SOSIALISASI PERHITUNGAN DAN PELAPORAN PAJAK UNTUK KOPERASI DIKABUPATEN SIDRAP: SOSIALISASI PERHITUNGAN DAN PELAPORAN PAJAK - Dahniyar Daud Daud (Nobel Community Services Journal, 2022)
The purpose of this training is to increase understanding of calculation techniques and Sidenreng Rappang (Sidrap). Participants in this training are managers and persons in charge of each Cooperative registered in Sidrap Regency. This research method uses a participatory approach with the presentation of material in the form of lectures by competent speakers in their fields followed by discussions and hands-on training on tax calculation and reporting for cooperatives. The results of this training show that the socialization of tax calculation and reporting for cooperatives can improve the knowledge skills of managers in understanding tax calculation and reporting techniques for cooperatives